Relationships between force-time characteristics of the isometric midthigh pull and dynamic performance in professional rugby league players - West, D. J.; Owen, N. J.; Jones, M. R.; Bracken, R. M.; Cook, C. J.; Cunningham, D. J.; Shearer, D. A.; Finn, C. V.; Newton, R. U.; Crewther, B. T.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2011)
There is considerable conflict within the literature regarding the relevance of isometric testing for the assessment of neuromuscular function within dynamic sports. The aim of this study was to determine the relationship between isometric measures of force development and dynamic performance. Thirty-nine professional rugby league players participated in this study. Forty-eight hours after trial familiarization, participants performed a maximal isometric midthigh pull, with ~120-130° bend at the knee, countermovement jump (CMJ), and a 10-m sprint. Force-time data were processed for peak force (PF), force at 100 milliseconds (F100ms), and peak rate of force development (PRFD). Analysis was carried out using Pearson's product moment correlation with significance set at p < 0.05. The PF was not related to dynamic performance; however, when expressed relative to body weight, it was significantly correlated with both 10-m time and CMJ height (r = -0.37 and 0.45, respectively, p < 0.05). The F100ms was inversely related to 10-m time (r = -0.54, p < 0.01); moreover, when expressed relative to body weight, it was significantly related to both 10-m time and CMJ height (r = -0.68 and 0.43, p < 0.01). In addition, significant correlations were found between PRFD and 10-m time (r = -0.66, p < 0.01) and CMJ height (r = 0.387, p < 0.01). In conclusion, this study provides evidence that measures of maximal strength and explosiveness from isometric force-time curves are related to jump and sprint acceleration performance in professional rugby league players.